Nurses' adaptations to changes on a COVID-19 ward in South Korea: A qualitative study. Issue 3 (March 2023) - Lee, Won; Pyo, Jeehee; Ock, Minsu; Jang, Seung Gyeong; Choi, Eun Young
Abstract: Background: Elucidating nurses' adaptation to changes in the early stage of an infectious disease epidemic is necessary to promote nurses' coping with and adapting to situations in which new infectious diseases are predicted periodically. Aim: To explore nurses' adaptation to changes in COVID-19 wards in South Korea. Methods: In-depth interviews were conducted with 20 nurses through purposive sampling from May to August 2020. The collected data were transcribed verbatim, and analysis was performed using conventional content analysis. Findings: Three categories emerged from the interviews: (a) Disruption caused by an unforeseen pandemic outbreak, (b) perseverance through the turmoil of changes as a nurse, and (c) transition from feelings of fearfulness to those of accomplishment. While the nurses initially struggled to care for patients with COVID-19, they made conscious efforts to provide emotional nursing and maintain their professionalism. Discussion: Nurses caring for patients with COVID-19 have faced a number of challenges but have adapted to new scenarios by endeavoring to fulfil their professional roles. Conclusion: To overcome a national disaster situation such as COVID-19, the government and healthcare organizations should prepare strategies to support the efforts of nurses to strengthen their own professionalism.